Saccadic intrusions in amyotrophic lateral sclerosis (ALS) - Wolfgang Becker; Martin Gorges; Dorothée Lulé; Elmar Pinkhardt; Albert Christian Ludolph; Jan Kassubek (Journal of Eye Movement Research, 2019)
The attempt to steadily fixate at a small visual object is continuously interrupted by a variety of fixational eye movements comprising, among others, a continuum of saccadic intrusions (SI) which ranges in size from microsaccades with amplitudes ≤0.25° to larger refixation saccades of up to about 2°. The size and frequency of SI varies considerably among individuals and is known to increase in neurodegenerative diseases such as neurodegenerative parkinsonism and amyotrophic lateral sclerosis (ALS). However, studies of ALS disagree whether also the frequency of SI increases. We undertook an analysis of SI in 119 ALS patients and 47 age-matched healthy controls whose eye movements during fixation and tests of executive functions (e.g antisaccades) had been recorded by video-oculography according to standardised procedures. SI were categorised according to their spatio-temporal patterns as stair case, back-and-forth and square wave jerks (a subcategory of back-and-forth). The SI of patients and controls were qualitatively similar (same direction preferences, similar differences between patterns), but were enlarged in ALS. Notably however, no increase of SI frequency could be demonstrated. Yet, there were clear correlations with parameters such as eye blink rate or errors in a delayed saccade task that suggest an impairment of inhibitory mechanisms, in keeping with the notion of a frontal dysfunction in ALS. However, it remains unclear how the impairment of inhibitory mechanisms in ALS could selectively increase the amplitude of intrusions without changing their frequency of occurrence.